Chemokine-like factor-like MARVEL transmembrane domain containing 6: Bioinformatics and experiments in vitro analyze in glioblastoma multiforme - Meng, Haining; Li, Shaohua; Li, Qingshu; Wang, Yuqin; Wang, Guoan; Qu, Yan (Frontiers in Molecular Neuroscience, 2023)
Chemokine-like factor (CKLF)-like MARVEL transmembrane domain containing 6 (CMTM6) is a protein localized to the cell membrane and is known for its ability to co-localize with PD-L1 on the plasma membrane, prevent PD-L1 degradation, and maintain PD-L1 expression on the cell membrane. CMTM6 is highly expressed and plays an important role in various tumors such as oral squamous cell carcinoma (OSCC) and colorectal cancer (CRC), however, its role in Glioblastoma multiforme (GBM) is unclear. In this paper, to investigate the role of CMTM6 in GBM, we analyzed the expression of CMTM6 in GBM, the interaction with CMTM6 and the associated genes by bioinformatics. Importantly, we analyzed the expression of CMTM6 in GBM in relation to tumor-infiltrating lymphocytes (TILs), immunoinhibitors, immunostimulators, chemokines and chemokine receptors, and concluded that CMTM6 is closely related to the immune microenvironment and inflammatory response in GBM. In order to understand the functional role of CMTM6 in GBM, we further analyzed the function of CMTM6 and performed in vitro experiments to verify it. It was demonstrated that CMTM6 significantly promoted the migration of GBM cells and epithelial-mesenchymal transition (EMT), but had no significant effect on other functions. Interestingly, bioinformatics analysis also revealed that CMTM6 was associated with the sensitivity of various drugs, so we validated the relationship between CMTM6 and the anticancer drug Piperlonguminine (PL) in vitro. In this paper, we have performed a detailed analysis and validation of the role of CMTM6 in GBM using bioinformatics analysis and in vitro experiments to demonstrate that CMTM6 may be a potential target for glioma therapy.